Programme standards medical and health sciences 2025 - Abdullah, Ahmad Fahmi Lim; Appukutty, Mahenderan; Haw, Chang Kah; Norazit, Anwar; Salleh, Mohd Nazil; Suid, Asmaa'; Ishak, Wan Syafira; Jamaluddin, Saiful Adli; Zakaria, Mohd Normani; Che Husin, Siti Suriani; Anual, Muhammad Shafiq Imran; Abu Bakar, Nurulamin; et al. (Malaysian Allied Health Professions Council, 2025)
The Programme Standards: Medical and Health Sciences (2025) serves as a guide to the Higher Education Providers (HEPs) in designing and offering academic programmes pertaining to the field of medical and health sciences in Malaysia at tertiary levels. The programme standards (PS) also takes into consideration the need to provide flexibility for HEPs to exercise innovation in offering academic programmes to meet the current and future needs in medical and health science education and training based on different modes of study*. Section A of this PS describes the general standards that provide supplemental requirements that build upon the foundation of the Code of Practice for Programme Accreditation (COPPA) for medical and health science programmes. In addition, discipline-specific requirements for the respective disciplines at Diploma (Level 4), Bachelor’s Degree (Level 6), Master’s Degree by coursework, mixed-mode and research (Level 7), and Doctoral Degree by coursework, mixed-mode and research (Level 8) are further described in Section B, Section C, Section D and Section E, of this PS, respectively.